A complex renal mass: always a malignancy? - Kulkarni, Shrirang V.; Jafri, Haris (International Surgery Journal, 2022)
A complex renal mass arousing suspicion of malignancy warrants exploration. Echinococcal etiology without any other organ involvement is a rarity. Experience with such a singular case managed laparoscopically is presented and discussed.